The effect of special exercises to develop the motor coordination on learning some basics skills of lown tennis for the physical education college - Jalal, Ali (Journal of Physical Education, 2010)
The thesis includes five parts , whereas, the first part includes the thesis itself and its significance, and we had talked bout the problem of the thesis ,and its targets, it s supposes and at last the three demotions of the research place ,time ,and humanitarian .The Chapter three describes the methods of research and its field procedures the subjects are described in details in this chapter .twenty students have been chosen and divided in to two groups :controlling and experimental each of ten (10) students the pilot study as well as the pretest and its application to the menu experiment have been introduced the students of the pilot study sports clus and badminton are excluded the chapter also describes the post test used and the statistical analysis.The fourth part , had talked showing and analysis and discussion the results of the thesis which he reached and known the method of developing the The basics skills and super. The fifth part talked about the conclusion and recommendations that given by the researcher, as the research had talked about program of Training unit.